Satellite observations of plasma-wave disturbances induced by high-power radio emission from the NWC transmitter - Belov, A.S.; Markov, G.A.; Parrot, М. (Вопросы атомной науки и техники, 2013)
In this work, we present the results of in-situ measurements of the characteristics of electromagnetic and plasma disturbances in the ionospheric region modified by high-power emission from the NWC transmitter, which were obtained using the onboard equipment of the French microsatellite DEMETER. It is shown that under the influence of VLF emissions from the ground-based transmitters, artificial plasma-wave channels with typical transverse scales of about 1000 km can be formed in the ionospheric plasma. Представлены результаты непосредственных (in-situ) измерений бортовой аппаратурой французского микроспутника DEMETER характеристик электромагнитных и плазменных возмущений в модифицированной мощным излучением передатчика NWC области ионосферы. Отмечено, что при воздействии ОНЧ-излучения наземных передатчиков в ионосферной плазме формируются искусственные плазменно-волновые каналы с характерным поперечным масштабом ~ 1000 км. Представлені результати безпосередніх (in-situ) вимірювань бортовою апаратурою французького мікросупутника DEMETER характеристик електромагнітних і плазмових збурень у модифікованій потужним випромінюванням передавача NWC області іоносфери. Відзначено, що при впливі ОНЧ- випромінювання наземних передавачів в іоносферній плазмі формуються штучні плазмово-хвильові канали з характерним поперечним масштабом ~ 1000 км.